2021
DOI: 10.1115/1.4052710
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Reduction of High-Fidelity Machine Tool Models by Using Global Sensitivity Analysis

Abstract: Models that are able to accurately predict the dynamic behavior of machine tools are crucial for a variety of applications ranging from machine tool design to process simulations. However, with increasing accuracy, the models tend to become increasingly complex, which can cause problems identifying the unknown parameters which the models are based on. In this paper, a method is presented that shows how parameter identification can be eased by systematically reducing the dimensionality of a given dynamic machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In other words, modes can be found that are only affected by a handful of model parameters, leading to the desired partitioning of the overall identification problem. More information can be found in [20], where this was already shown exemplarily.…”
Section: Partitioning Of the Overall Identification Problem Via Gsasmentioning
confidence: 77%
See 4 more Smart Citations
“…In other words, modes can be found that are only affected by a handful of model parameters, leading to the desired partitioning of the overall identification problem. More information can be found in [20], where this was already shown exemplarily.…”
Section: Partitioning Of the Overall Identification Problem Via Gsasmentioning
confidence: 77%
“…As the model's damping parameters do not influence the simulated mode shapes and eigenfrequencies (see Assumption A1 in Section 2.1), the overall identification problem can be further simplified by determining the stiffness parameters first. The partitioning via GSAs leads to N modes N pos (see Equation ( 10)) identification problems with only a handful of search parameters each [20]. Even though the partitioning eliminates most of the local minima of the overall optimization problem, which would lead to only locally valid and non-physical machine tool model parameters, some are still present [20].…”
Section: Stiffness Parameter Identificationmentioning
confidence: 99%
See 3 more Smart Citations